PENGENALAN KONSEP COMMUNITY-BASED TOURISM DALAM MENDUKUNG PENGEMBANGAN DESA TUMBUK TEBING MENJADI DESA WISATA - Saputri, Dwi Oktavallyan; Seftyarizki, Debby; Safrianti, Sintia (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Kristen Duta Wacana, 2025)
An attractive tourist village is a village that has its uniqueness and characteristics, both from its natural beauty, and culture and also the potential of its human resources. The concept of a tourist village will have a positive impact on a village in preserving the nature and culture of the village and requires community participation so that the community itself has a high sense of ownership and feels the benefits of the existence of a tourist village. Tumbuk Tebing Village is a village that is starting to pioneer in making this area a tourist village, starting to explore the existing tourism potential and introducing it to the tourism industry. The management of a locally-based tourist village requires the concern and participation of the community itself always to innovate and be creative in developing their village area which is used as a tourist village. This community service is carried out by providing initial knowledge related to tourism villages, especially seeing the potential in the Tumbuk Tebing Village Area, South Bengkulu Regency, including beaches with white rocks, rice fields, habitat for white stork colonies, swamp birds, and a strong rural environment that can be packaged in the concept of Community-based Tourism, conducting question and answer discussions, and conducting surveys on attractions, accessibility, and existing facilities. This community service activity is expected to help Tumbuk Tebing Tourism Village, South Bengkulu Regency, in realizing becoming a tourist destination.